PENGARUH PENGETAHUAN PERPAJAKAN, KESADARAN WAJIB PAJAK, SANKSI PAJAK, TINGKAT KEPERCAYAAN PADA PEMERINTAH, DAN KUALITAS PELAYANAN TERHADAP KEPATUHAN WAJIB PAJAK BUMI DAN BANGUNAN (Survei Pada Wajib Pajak Bumi dan Bangunan di Desa Masaran Kecamatan Masaran Kabupaten Sragen) - Safitri, Priyanis Wahyu; Harimurti, Fadjar; Sunarti, Sunarti (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2021)
This study aims to determine the effect of tax knowledge, taxpayerawareness, tax sanctions, level of trust in the government, and service quality onland and building taxpayer compliance in Masaran Village, Masaran District,Sragen Regency. This type of research is a survey on PBB taxpayer in MasaranVillage, Masaran District, Sragen Regency. The population of this research is allPBB taxpayers registered in Masaran Village, Masaran District, Sragen Regency.The sampling technique used Quota sampling with a sample percentage of 100PBB taxpayers. The data collection technique used a questionnaire. The dataanalysis technique used is multiple linear regression. The results showed that taxknowledge had an effect on PBB taxpayer compliance in Masaran Village,Masaran District. Taxpayer awareness has an effect on PBB taxpayer compliancein Masaran Village, Masaran District. Tax sanctions affect the compliance ofPBB taxpayers in Masaran Village, Masaran District. The level of trust in thegovernment affects the compliance of PBB taxpayers in Masaran Village,Masaran District. Service quality affects PBB taxpayer compliance in MasaranVillage, Masaran District.